2020
DOI: 10.1186/s12906-020-2862-4
|View full text |Cite
|
Sign up to set email alerts
|

Bioactivity evaluations of leaf extract fractions from young barley grass and correlation with their phytochemical profiles

Abstract: Background: The pressed juice of Barley Grass (BG) has become very popular among people for various assumed benefits along with many testimonies of people who have been healed from various ailments such as anemia, cancer, GI problems by consuming BG. The aim of our research was to validate the claims of its medicinal values such as chemo-protective action, high anti-oxidants, RBC membrane stabilization activity, and toxicity level. Methods: Extracts of hexane, ethyl acetate and methanol were quantitatively est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 36 publications
1
24
1
Order By: Relevance
“…In an experiment conducted by Samsonowicz and Regulska (2018), aqueous extracts of barley seedlings were characterized by TPC values up to 10.7 mg GAE/g and ethanolic extracts up to 10.9 mg GAE/g [63]. A study by Panthi et al (2020) showed that the methanolic extract of young barley juice had the highest polyphenol content (82.56 mg GAE/g) [64].…”
Section: Discussionmentioning
confidence: 99%
“…In an experiment conducted by Samsonowicz and Regulska (2018), aqueous extracts of barley seedlings were characterized by TPC values up to 10.7 mg GAE/g and ethanolic extracts up to 10.9 mg GAE/g [63]. A study by Panthi et al (2020) showed that the methanolic extract of young barley juice had the highest polyphenol content (82.56 mg GAE/g) [64].…”
Section: Discussionmentioning
confidence: 99%
“…It might be due to the presence of phytochemicals such as flavonoids, terpenoids, steroids, tannin, and phenolic compounds which were identified to promote wound healing activity mainly because of their antibacterial and antioxidant activity (10, 16-17, 21,39). Many studies has reported the role of phytochemicals in wound healing as tannins are seen to be active detoxifying agents and inhibit bacterial growth (42), terpenoids have astringent and antimicrobial property which promote the wound healing process (43), flavonoids and polyphenols shows the antioxidants activity by scavenging the free radical and possess anti-inflammatory properties and have antimicrobial activities (44)(45)(46)(47)(48)(49). Therefore, phytochemicals present in the crude extract may contribute to wound healing activities independently or synergistic effects.…”
Section: Discussionmentioning
confidence: 99%
“…The major phytocomponents reported were dodecane, 9-octadecenoic acid, and ethyliso-allocholate. Panthi et al [59] also found that the GC-MS analysis of a methanolic extract of barley grass contained fatty acids like 13-docosenic acid and 9,12,15octadecatrienoic acid. They have cancer-preventive, nematicide, anti-arthritic, antiandrogenic, anti-inflammatory, and hypocholesterolemic properties [60].…”
Section: Chemical Composition and Gc-ms Analysis Of Wheat And Barleymentioning
confidence: 98%